Molecular Determinants of the Promiscuity of MexB and MexY Multidrug Transporters of Pseudomonas aeruginosa - Ramaswamy, Venkata K.; Vargiu, Attilio V.; Malloci, Giuliano; Dreier, Jürg; Ruggerone, Paolo (Frontiers in Microbiology, 2018)
Secondary multidrug transporters of the Resistance-Nodulation-cell Division (RND) superfamily contribute crucially to antibiotic resistance in Gram-negative bacteria. Compared to the most studied transporter AcrB of Escherichia coli, little is known about the molecular determinants of distinct polyspecificities of the most important RND transporters MexB and MexY of Pseudomonas aeruginosa. In an effort to add knowledge on this topic, we performed an exhaustive atomic-level comparison of the main putative recognition sites (access and deep binding pockets) in these two Mex transporters. We identified an underlying link between some structural, chemical and dynamical features of the binding pockets and the physicochemical nature of the corresponding substrates recognized by either one or both pumps. In particular, mosaic-like lipophilic and electrostatic surfaces of the binding pockets provide for both proteins several multifunctional sites for diffuse binding of diverse substrates. Specific lipophilicity signatures of the weakly-conserved deep pocket suggest a key role of this site as a selectivity filter as in Acr transporters. Finally, the different dynamics of the bottom-loop in MexB and MexY support its possible role in binding of large substrates. Our work represents the first comparative study of the major RND transporters in P. aeruginosa and also the first structure-based study of MexY, for which no experimental structure is available yet.